Brief Report: Hospitalization Rates Among Persons With HIV Who Gained Medicaid or Private Insurance After the Affordable Care Act in 2014. (1st June 2021) - Chow, Jeremy Y.; Nijhawan, Ank E.; Mathews, W. Christopher; Raifman, Julia; Fleming, Julia; Gebo, Kelly A.; Moore, Richard D.; Berry, Stephen A.
Abstract : Background: It is unknown whether gaining inpatient health care coverage had an effect on hospitalization rates among persons with HIV (PWH) after implementation of the Affordable Care Act in 2014. Methods: Hospitalization data from 2015 were obtained for 1634 adults receiving longitudinal HIV care at 3 US HIV clinics within the HIV Research Network. All patients were engaged in care and previously uninsured and supported by the Ryan White HIV/AIDS Program in 2013. We evaluated whether PWH who transitioned to either Medicaid or private insurance in 2014 tended to have a change in hospitalization rate compared with PWH who remained uncovered and Ryan White HIV/AIDS Program supported. Analyses were performed by negative binomial regression with robust standard errors, adjusting for gender, race/ethnicity, age, HIV risk factor, CD4 count, viral load, clinic site, and 2013 hospitalization rate. Results: Among PWH without inpatient health care coverage in 2013, transitioning to Medicaid [adjusted incidence rate ratio 1.26, (0.71, 2.23)] or to private insurance [0.48 (0.18, 1.28)] in 2014 was not associated with 2015 hospitalization rates, after accounting for demographics, HIV characteristics, and prior hospitalization rates. The factors significantly associated with higher hospitalization rates include age 55–64, CD4 <200 cells/µL, viral load >400 copies/mL, and 2013 hospitalization rate. Conclusions: Acquiring inpatient coverage was not associated with a change in hospitalization rates. These results provide some evidence to allay the concern that acquiring inpatient coverage would lead to increased inpatient utilization. Abstract : Supplemental Digital Content is Available in the Text.